RISE: Embracing sustainability via academic endeavours / Prof. Dr Corina Joseph - Joseph, Corina (Office of the Deputy Vice-Chancellor (Research & Innovation), 2022)
Sustainability has been an ongoing area of interest for Prof. Dr Corina since her PhD completion in 2010. Her thesis title was ‘Sustainability Reporting on Malaysian Local Authority Websites’ – examining the extent of sustainability information disclosure and the factors influencing the level of sustainability information using the isomorphism conception from the lens of institutional theory.